Construction of Index System for Risk Assessment in Supply Chains of Automotive Industry - Muhammad Junaid; Xue Ye; Syed Muzzammil Wasim (International Journal of Supply Chain Management, 2020)
Automotive industry in Pakistan plays an important role in the economy and is exposed to a variety of supply chain risks but is underprivileged in terms of research. Therefore, to inform the effective and efficient development of the automotive industry, this paper analyses the key risk sources for supply chains of automotive firms using 3 primary sources, 6 secondary sources and 35 risks established from the existing literature on supply chain risk. To testify the proposed index system, data of 101 questionnaires were employed to SPSS 25 to perform reliability and validity checks. Afterwards, factors analysis was performed to get the final risk assessment index system, which confirmed that supply chain risks in the automotive industry are classified in three primary sources, internal risks, external risks and stream risks. Six secondary sources, macro risks, industry risks, organizational risks, operational risks, upstream risks and downstream risks; and 35 risks in total.